(untitled) (The International Journal for Scientific Research, 2026)
The principle of the independence of the arbitration clause means that the arbitration clause included in a contract is considered an agreement independent of the original contract, despite being linked to it. Accordingly, the invalidity, rescission, or termination of the contract does not automatically invalidate the arbitration clause unless the defect pertains to the clause itself. This principle aims to protect the parties’ will to resort to arbitration as a means of dispute resolution and to prevent any party from evading arbitration by challenging the original contract. The Saudi legal system has adopted this principle in line with modern international trends in arbitration, thereby enhancing the stability of commercial transactions and increasing confidence in the investment environment. This study examines judicial and arbitration applications in the Kingdom of Saudi Arabia, comparing them with international legislation, regulations, and comparative laws to highlight points of agreement and difference, and the effectiveness of the principle in guaranteeing the independence of the arbitration process.